PENGARUH BUDAYA ORGANISASI DAN DIKLAT TERHADAP KINERJA PEGAWAI DI LEMBAGA PEMASYARAKATAN NARKOTIKA KLAS IIA KABUPATEN MUSI RAWAS - Bobbi Kusbeini; Abdullah Hehamahua; Betti Nuraini (Jurnal Interprof, 2017)
The purpose of this study to find how the influence of Organizational Culture and Training on Employee Performance in Class Iark Drug Prison Class IIA Musi Rawas District. From the calculation of coefficient of determination obtained the value of R is 0.701. This means a positive relationship between the Culture of Organisasi and Diklat on Employee Performance in Class Iark Drug Prison Class IIA Musi Rawas Regency is very strong, If Organizational Culture and TrainingIncreased then Performance of employees also increases. Then from the calculation of the coefficient of determination (R2) of 0.491. Means that the magnitude of the influence of Culture Oraganisasi and Diklat on Employee Performance in Prison Class IIA Narcotics District Musi Rawas equal to 0.491 or 49.1%, while the remaining 50.9%. Influenced other variables that are not included in this study such as variable motivation, supervision and so on. Simultaneously organizational culture and dilat effect on performance. The results of this study may be used by subsequent researchers, as research materials in the field of science of organizational behavior or similar science.